If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 40 = -10x Solving 40 = -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 40 + 10x = -10x + 10x Combine like terms: -10x + 10x = 0 40 + 10x = 0 Add '-40' to each side of the equation. 40 + -40 + 10x = 0 + -40 Combine like terms: 40 + -40 = 0 0 + 10x = 0 + -40 10x = 0 + -40 Combine like terms: 0 + -40 = -40 10x = -40 Divide each side by '10'. x = -4 Simplifying x = -4
| 3x-2x+7x=-24 | | 12-17=139 | | 3y+9=5y-3y | | -2n+6n=16 | | -1.4=2x | | 25x^2+10x+-8= | | 8D=5F | | -8(3b+4)+(25b-5)=0 | | -6f+13=2f | | 5+4(3x-8)-2(x+6)=x-9 | | 8n+22=-2(-4n+3)+7n | | r+8.4=-0.5 | | 6=-3(r+2) | | w^2+2w=99 | | 4a=a-18 | | 2=2x-6 | | -3n+30=-6(6+6n) | | 3x^3+25=x^2+75 | | 13=3n+6-8 | | 8b-12b+10b= | | x^2+3x-72=4x | | 9l=3l+3m | | 0.66X-16=0 | | 6(w-1)=3(w+5) | | 26-5x=-7(x-4) | | (-8y-5)(7y)*y=-3 | | 5p+2=11+4p | | 57=-7(7b-3)-(7-6b) | | 6x+6=3x | | 26-5x=-7-3r | | 4(u-4)-6u=4 | | 20-4(2w+1)=6w-4(6+w) |